Neural-Inflammation Mechanism of Spinal Palmitic Acid Promoting Atopic Dermatitis in Mice - Yang J; Xue X; Yang Z; Hao F; Chen B (Journal of Inflammation Research)
Jing Yang,1 Xiaoling Xue,2 Zhi Yang,1 Fei Hao,1 Bangtao Chen3 1Department of Dermatology, Third Affiliated Hospital of Chongqing Medical University, Chongqing, 401120, People’s Republic of China; 2Department of Pathogenic Biology, College of Basic Medical Sciences, Jinzhou Medical University, Jinzhou, 121001, People’s Republic of China; 3Department of Dermatology, Chongqing University Three Gorges Hospital, School of Medicine, Chongqing University, Chongqing, 404000, People’s Republic of ChinaCorrespondence: Fei Hao, Email 651588@hospital.cqmu.edu.cn Bangtao Chen, Email medisci@163.comObjective: To profile spinal medium- and long- chain fatty acids (ML-CFAs) and itch-related gene expressions (IRGEs) in dorsal root ganglion (DRG), and investigate the role of spinal palmitic acid (PA) in atopic dermatitis (AD), and its relationship with DRG and spinal extracellular signal-regulated kinase (ERK).Methods: MC903 was applied topically to the nape of C57BL/6 mice to induce AD. Two doses of PA were administered intrathecally during MC903 treatment, and several antagonists were administered intrathecally one day before PA challenge. Transcriptome sequencing was performed on DRGs, and 36 ML-CFAs in the spinal cord were analyzed.Results: A global upregulation of IRGEs in DRGs and increases in major ML-CFAs including PA in the spinal cord were observed in adult AD model. MC903 resulted in less severe dermatitis with weaker IRGEs in DRGs and lower spinal ML-CFAs in senile than adult mice. In adult mice, intrathecal PA injection caused acute scratches, aggravated AD, and induced stronger IRGEs in DRGs. Intrathecal injection of transient receptor potential vanilloid-1 channel (TRPV1) antagonist capsazepine or Mas-related G protein-coupled receptor D (MRGPRD) antagonist d-Pro7-ANG-(1-7) remarkably halted PA/MC903-induced dermatitis and PA-induced scratching. Administration of histamine h4 receptor antagonist JNJ7777120 only moderately alleviated dermatitis, with no notable effect on scratches. Intrathecal pan-palmitoylation inhibitor 2-Bromopalmitate moderately alleviated MC903/PA-induced lesions and spinal ERK phosphorylation. Intrathecal lidocaine markedly suppressed both lesions and ERK phosphorylation, along with a global reduction in IRGEs in DRGs. Finally, PA-induced scratches were significantly improved by intrathecal lidocaine but not 2-Bromopalmitate.Conclusion: MC903-induced AD develops more readily in adult than senile mice, with consistent changes in IRGEs in DRG and spinal ML-CFA levels, including PA. Spinal PA promotes AD involving spinal TRPV1 and MRGPRD signaling, and IRGEs increments in DRG. Intrathecal lidocaine suppresses AD aggravated by PA via inhibiting spinal ERK phosphorylation and reducing IRGEs in DRG.Keywords: Atopic dermatitis, Palmitic acid, Dorsal root ganglion, Spinal cord, Extracellular signal-regulated kinase, Transcriptome sequencing